The role of the psychologist in the palliative care service of a tertiary hospital in Ceará state, Brazil : an experience report (Brazilian Journal of Health Research, 2025)
Introduction: Palliative care aims to improve the quality of life of patients and their families facing life-threatening illnesses. A palliative care service is composed of an interprofessional team, minimally including physicians, psychologists, nurses, and social workers. Objective: To report the author’s experience as a psychologist in a palliative care service. Methods: This is a descriptive, qualitative study in the form of an experience report, conducted in a tertiary hospital located in Fortaleza, Ceará, Brazil. Results: Psychological support may be offered to both patients and family members, either through active outreach or upon request from the team. Assistance often begins when the illness is already at an advanced stage. Among the various possible interventions, the psychologist may play a key role in facilitating difficult conversations and family conferences. Conclusion: Interventions that could be initiated at the time of diagnosis are often delayed until the end-of-life stage, already marked by suffering and exhaustion, which limits the work not only of the psychologist but of the entire care team.
Keywords: Palliative Care; Hospital Psychology; Health Communication